PENERAPAN FUNGSI KELUARGA ERA CYBERSPACE DI KELURAHAN CATUR RUNGGAL SLEMAN YOGYAKARTA (PENDEKATAN KOMUNIKASI INTERPERSONAL): PENERAPAN FUNGSI KELUARGA ERA CYBERSPACE DI KELURAHAN CATUR RUNGGAL SLEMAN YOGYAKARTA (PENDEKATAN KOMUNIKASI INTERPERSONAL) - mike meiranti (Indonesian Journal of Islamic Communication, 2019)
Family is a relationship that is bound by marriage ropes where in fostering the family of husband and wife have the best hope for the continuity of the family. Basically the formation of a family is to carry out family functions in order to form a happy happy family, family functions such as religion, education, social, protection, intuition, economy, recreation, and bilological. However, in the development of the world of cyberspace family functions have begun to shift its application, this is due to the development of cyberspace which has formed a new pattern of thinking, lifestyle and orientation in a family so that families who cannot control the development of cyberspace will be vulnerable to internal conflicts and will adversely affect developing children if parents tend to be busy with their activities in cyberspace compared to the real world. Seeing this reality, the most effective thing for the application of family functions to work well is by interpersonal communication between each family member. Where culture of communication becomes a powerful weapon in carrying out the roles and functions in the household. In this paper researchers will use qualitative methods that are descriptive